Mustansir Mir and a Contemporary Literary Approach to the Qaṣaṣ al-Qur’ān: Study of Qur’anic Story of Joseph - Akrimi Matswah (Universitas Islam Negeri Mataram, 2017)
The textuality of the Qur'an contains a high quality of literary aspect. Therefore, a literary approach to the Qur’an is one of the ways in the understanding of the meaning and message of it. This approach has been used by modern and contemporary Muslim scholars, and even by western scholars of Qur’an studies. This paper discusses Mustansir Mir’s thought and literary approach to the Qur’an, focusing on the story of Joseph. This study shows that Mir reflects on the nature and power of God and reveals the moral messages in the scene and structured dialogue on the passages in Sūra Yūsuf. It also reveals that Mir’s approach to the story is structural where he elaborates the structure, plot, and scene of the story and connects them with the moral message of the story.